Slip-rolling behavior of ductile and austempered ductile iron containing niobium or chromium - Pimentel A.S.O.* (2019)
Copyright © 2019 by ASTM International.The use of high niobium alloyed cast iron alloys is a relatively new approach in which the niobium addition intends to improve the properties of the material by the precipitation of hard niobium carbides during solidification. Steels can be replaced by ductile cast iron in some rolling applications, such as gears and cams, in order to reduce material costs. The aim of this work is to evaluate ductile iron alloyed with 1 weight percent (wt.%) niobium for the as cast specimens and with 1.8 wt.% and 2.4 wt.% niobium for the austempered specimens under lubricated slip-rolling tests using mixed/boundary conditions in an Amsler-type machine. Austempered ductile iron (ADI) alloyed with 1 wt.% chromium, or Carbidic ADI, was tested for comparison. For the as cast conditions, the niobium addition resulted in an increase of wear resistance owing to the low contact pressure of these tests. However, for the austempered specimens, the best performance was found for unalloyed ADI. The main factor acting in the initiation and propagation of cracks in ductile iron is the presence of the graphite nodules. The coarse carbides also contributed to the initiation of cracks and spalling of the material.